2003
DOI: 10.1149/1.1554913
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Localized Degradation of Organic Coatings

Abstract: The degradation of polyester coil-coated galvanized steel was compared using both conventional ͑macroscopic͒ and localized electrochemical impedance techniques on the same specimen and within a time interval ͑hours͒ much shorter than the total immersion period ͑days͒. Specimens containing a central 250 m laser-ablated defect in the organic coating layer were immersed in a 10 mM NaCl solution for up to 30 days. The local multifrequency impedance was determined by placing a novel impedance probe, either directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 14 publications
1
25
0
1
Order By: Relevance
“…1). The border of LEIM response, where z −1 (r) approaches zero, is at about 5 mm that is 2-3 times larger than the actual radius of the WE (2 mm), which is in a good agreement with the literature [7,[15][16][17][18].…”
Section: Numerical Simulations Of Leim Experimentssupporting
confidence: 89%
See 3 more Smart Citations
“…1). The border of LEIM response, where z −1 (r) approaches zero, is at about 5 mm that is 2-3 times larger than the actual radius of the WE (2 mm), which is in a good agreement with the literature [7,[15][16][17][18].…”
Section: Numerical Simulations Of Leim Experimentssupporting
confidence: 89%
“…Maps of the local impedance, z(r), or the local admittance, z −1 (r), at fixed frequency are the typical output used so far in the literature to report on LEIM experiments [7,[15][16][17][18], but in the present work only the local admittance has been used.…”
Section: Electrochemical Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…This point is important because it emphasizes that, depending on the probe size, information can be obtained at different scales. Using a similar technique, Philippe et al [37] investigated polymer-coated galvanized steel. They showed that the global electrochemical impedance measurements provided surface-averaged responses corresponding to both the polymer properties and its defects, whereas LEIS allowed coating defects to be isolated.…”
Section: Introductionmentioning
confidence: 99%